Patterns and risk factors for deaths from external causes in rural Malawi over 10 years: a prospective population-based study. (December 2015) - Chasimpha, Steady; McLean, Estelle; Chihana, Menard; Kachiwanda, Lackson; Koole, Olivier; Tafatatha, Terence; Mvula, Hazzie; Nyirenda, Moffat; Crampin, Amelia; Glynn, Judith
Abstract Background Little is known about the pattern or risk factors for deaths from external causes in sub-Saharan Africa: there is a lack of reliable data, and public health priorities have been focussed on other causes. This study assessed the prevalence and risk factor for deaths from external causes in rural Malawi. Methods We analysed data from 2002–2012 from the Karonga demographic surveillance site which covers ~35, 000 people in rural northern Malawi. Verbal autopsies with clinician coding are used to assign cause of death. Repeated annual surveys capture data on socio-economic factors. Using Poisson regression models we calculated age, sex and cause-specific rates and rate ratios of external deaths. We used a nested case–control study, matched on age, sex and time period, to investigate risk factors for these deaths, using conditional logistic regression. Results In 315, 580 person years at risk (pyar) there were 2673 deaths, including 143 from external causes. The mortality rate from external causes was 47.1/100, 000 pyar (95 % CI 32.5-68.2) among under-fives; 20.1/100, 000 pyar (95 % CI 13.1–32.2) among 5–14 year olds; 46.3/100, 000 pyar (95 % CI 35.8–59.9) among 15–44 year olds; and 98.7/100, 000 pyar (95 % CI 71.8–135.7) among those aged ≥45 years. Drowning (including four deaths in people with epilepsy), road injury and suicide were the leading external causes. Adult males had the highest rates (100.7/100, 000 pyar), compared to 21.8/100, 000pyar in adult females, and the rate continued to increase with increasing age in men. Alcohol contributed to 21 deaths, all in adult males. Children had high rates of drowning (9.2/100, 000 pyar, 95 % CI 5.5-15.6) but low rates of road injury (2.6/100, 000 pyar, 95 % CI 1.0–7.0). Among 5–14 year olds, attending school was associated with fewer deaths from external causes than among those who had never attended school (adjusted OR 0.15, 95 % CI 0.08-0.81). Fishermen had increased risks of death from drowning and suicide compared to farmers. Discussion In this population the rate of deaths from external causes was lowest at age 5–14 years. Adult males had the highest rate of death from external causes, 5 times the rate in adult females. Drowning, road injury and suicide were the leading causes of death; alcohol consumption contributed to more than one quarter of the deaths in men Conclusions The high proportion of alcohol-related deaths in men, the predominance of drowning, deaths linked to uncontrolled epilepsy, and the possible protective effect of school attendance suggest areas for intervention.